Buckling of pre-twisted wires in polymeric matrix for future wearable electronic devices - Chua, Melvin Zhen Zhou (Nanyang Technological University, 2021)
In this report, we would be discussing about studying of shape memory effect of stiff layer matrix in embedded in a polymeric matrix. In this case, the polymeric matrix we would be using for experimentation would be gel wax. Gel wax was chosen as the polymeric matrix due to its transparency and the compressibility. The experiment would be conducted where different threads of materials would be embedded within the gel wax and later undergo compression to see if there is any buckling that would take place. We would also be looking out for whether the threads are able to return to their original shape after the load is removed. Various parameters were also introduced afterwards like pre-twisting the thread before embedding and the number of turns that we pre-twist the thread (0-100 turns) and whether the turns were in clockwise or anti-clockwise direction. Trends could be observed from the results that were obtained and different threads have been shown to react differently to different parameters. More research could be carried out in the future with introduction of new parameters or improve on the current experiment set up to test more materials to achieve new insights on the buckling of embedded stiff layer within polymeric matrix. There has been increasing interest in research of using buckled structures to improve the flexibility and durability of structures, through this experiments we hope to gain more insight to which materials may be suitable to be embedded as buckled structures in the near future.